CACCI country profile Colombia - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Colombia has focused on deepening the understanding of its vulnerability and risk to climate change. The Third National Communication on Climate Change (TCNCC) of 2017 shows that 13% of the departments are in the very high category of climate vulnerability. In addition, all of its territory has some level of threat due to climate change and 56% of the departments are in the very high threat category, as shown in its NDC 2020. One of the major concerns is that most of the country's emissions are generated by three important sectors: Agriculture, Land Use Change and Forestry, and Energy. These sectors are also highly vulnerable to climate impacts. The country has developed a significant number of policies and programs focused on climate change mitigation and adaptation, which take into account all stakeholders involved, from the public sector to the private sector and civil society recognizing that the implementation of the actions that the country has established is the responsibility of all actors.